Coronary Heart Disease: Diagnosis and Therapy - Iin Novita Nurhidayati Mahmuda; Nanda Nurkusumasari; Fakhri Nofaldi; Prihatin Puji Astuti; Ferika Dian Syafitri; Dessy Dessy (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2021)
Coronary heart disease (CHD), is one of the non-communicable diseases that has a tendency to increase every year and have an impact not only on developed countries, but also in developing countries. According to the World Health Organization (WHO), in 2012 there were 56 million deaths worldwide caused by non-communicable disease and heart disease contributed 46.2% or caused 17.5 million deaths. This review article to give brief explanation about CHD from risk factors, diagnosed criteria, management therapy and prognosis. Risk factors for CHD can be distinguished into major risk factors and minor risk factors. Symptoms of CHD are discomfort in the chest ranging from pain crushed during activity and improved with rest to continuous chest pain. The diagnosis of CHD is established based on anamnesis, physical examination, and laboratory examination. The CHD classification consists  of Stable Angina Pectoris (APS) and Acute Coronary Syndrome (ACS). Lifestyle changes accompanied by right medication can reduce complications caused             by CHD.